2012
DOI: 10.1007/s00023-012-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Locality and Covariance: What Makes a Physical Theory the Same in all Spacetimes?

Abstract: The question of what it means for a theory to describe the same physics on all spacetimes (SPASs) is discussed. As there may be many answers to this question, we isolate a necessary condition, the SPASs property, that should be satisfied by any reasonable notion of SPASs. This requires that if two theories conform to a common notion of SPASs, with one a subtheory of the other, and are isomorphic in some particular spacetime, then they should be isomorphic in all globally hyperbolic spacetimes (of given dimensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
170
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(171 citation statements)
references
References 57 publications
(113 reference statements)
1
170
0
Order By: Relevance
“…However, it is known that such an assignment of a state to a spacetime is impossible [HoWa01,BFV03,FeVe11]. Notwithstanding, this problem can be overcome if it is possible to restrict oneself to a limited class of spacetimes on which a unique state can be defined, this has been done in [Pin10].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is known that such an assignment of a state to a spacetime is impossible [HoWa01,BFV03,FeVe11]. Notwithstanding, this problem can be overcome if it is possible to restrict oneself to a limited class of spacetimes on which a unique state can be defined, this has been done in [Pin10].…”
Section: Discussionmentioning
confidence: 99%
“…A foundational problem for physics in curved spacetimes is to understand how a theory should be formulated such that its physical content is preserved across the various spacetimes on which it is defined; i.e., so that it represents the same physics in all spacetimes (SPASs) [FV12a]. This touches on what is actually meant by the physical content of a theory and it is not easy to make this mathematically precise.…”
Section: Maxwell Theories and Spassmentioning
confidence: 99%
“…On the other hand, all the theories discussed admit electromagnetic duality rotations as global symmetries. To conclude, we discuss three aspects in more detail, namely the status of dynamical locality, the categorical structure underlying some of our constructions, and the relation of our present work to the discussions of SPASs in [FV12a,FV12b].…”
mentioning
confidence: 99%
“…(3.1) gives the infinitesimal movement of the observables in the Hilbert-space representation of A (M, g (0) ) due to an infinitesimal perturbation ds around s = 0. Further properties and interpretations of this functional derivative and the relative Cauchy evolution can be found in [5,23,24]. For the case of the Klein-Gordon field, with its corresponding Weyl algebra of observables, it can be shown that both elements of this algebra and polynomials of field operators constructed from it obey the following relation (Theorem 4.3 from [5]):…”
Section: Relative Cauchy Evolutionmentioning
confidence: 95%
“…The approach has been used to develop a notion of "identical physics" on different spacetimes [23]. A key result is a method for calculating how quantum observables respond to local changes in the background spacetime.…”
Section: Relative Cauchy Evolutionmentioning
confidence: 99%